Correlation Between Transmission Prevention and Incidence of Filariasis: A Systematic Review - Nawan; Agatha, Sinda; Handayani, Septi; Toemon, Agnes Immanuela (Asian Journal of Health Research, 2025)
Introduction: Filariasis, a chronic infectious disease caused by filarial worms and transmitted by mosquitoes, remains a global public health issue, affecting 120 million people in 72 countries. Indonesia, with cases spread across 34 provinces, is one of the endemic countries. Preventive measures such as eliminating mosquito habitats, preventing mosquito bites, and implementing Mass Drug Administration (MDA) programs in endemic areas are essential to achieve filariasis elimination. This literature review aims to explore the correlation between these prevention practices and the incidence of filariasis to support elimination efforts. Material and Methods: Secondary data were sourced from databases including Google Scholar, PubMed, ResearchGate, SpringerLink, ScienceDirect, PLOS One, and Neliti. Using keywords such as prevention practices, Mass Drug Administration (MDA), risk factors, going out at night, bed nets, anti-mosquito repellent, wire netting, and filariasis, 30 research journals meeting the inclusion criteria and quality assessment were obtained. Results: The study results showed correlations between filariasis incidence and various prevention practices: 72.22% of studies (13 journals) with avoiding going out at night, 73.33% (11 journals) with using anti-mosquito repellent, 75% (12 journals) with using bed nets, 68.75% (11 journals) with using wire netting, and 92.31% (12 journals) with participating in Mass Drug Administration (MDA) programs. Conclusion: There were a correlation between no go out at night, the habit used of anti-mosquito repellent the used of bed net, wire netting, and taking Mass Drug Administration (MDA) programs with filariasis incidence.